Uzasadnienie namysłu nad partycypacją wyborczą w kontekście wyborów prezydenckich w Polsce w 2025 roku ………. 15 - Bujwid-Kurek, Ewa; Kiwior-Filo, Małgorzata; Banaś, Monika; Weżgowiec, Barbara (Wybory prezydenckie w Polsce w 2025 roku w świadomości najmłodszego elektoratu województwa małopolskiego, 2025)
RATIONALE FOR EXAMINING ELECTORAL PARTICIPATION IN THE CONTEXT OF THE PRESIDENTIAL ELECTIONS IN POLAND IN 2025The chapter Rationale for Examining Electoral Participation in the Context of the Presidential Elections in Poland in 2025 contains the main premises for undertaking research on the participation of the youngest electorate of Małopolska in the presidential elections in 2025. Despite numerous publications on civil society and electoral participation, the topic deserves in-depth scientific exploration. It constitutes a subject of dynamically changing reality, shaped by internal and external conditions, subjected to particular turbulence connected to the specificity of the years 2020-2025.